PERAN PENYULUHAN GIZI DENGAN DEMONSTRASI MASAK MP-ASI BERBASIS PANGAN LOKAl DALAM MENDUKUNG PEMBERIAN MAKAN BALITA YANG OPTIMAL - Azizah, Wafiq Nur; Hania Maria; Natasha Althafa; Nida Nurhikmah; Hurry Mega Insani (Jurnal ABDI: Media Pengabdian Kepada Masyarakat, 2026)
Indonesia still faces serious nutritional problems among children under five years of age due to inadequate food consumption and mothers' lack of knowledge about food selection and preparation. This condition leads to dependence on instant complementary foods (MP-ASI), resulting in suboptimal nutritional needs for children. TThis activity was carried out through an educational approach in the form of counseling and cooking demonstrations using local food ingredients. The results of the activity showed an increase in mothers' knowledge about MP-ASI, from an average score of 8.9/10 to 9.6/10. This activity had a positive impact in the form of improving mothers' skills in preparing complementary foods using local ingredients and raising awareness of the importance of choosing healthier foods for children. Based on these findings, nutrition education and cooking demonstrations on complementary feeding have been proven effective in supporting more optimal feeding practices for young children.